PENGARUH INTELLECTUAL CAPITAL PADA IBU RUMAH TANGGA TERHADAP KEBERHASILAN PENDIDIKAN ANAK DENGAN SOCIAL CAPITAL SEBAGAI VARIABEL MODERATING - Azmi, Fika; Wahyuni, Mirasanti; Imaningati, Sri (Program Studi Akuntansi, Universitas Kuningan, 2018)
Child education is very important to note because children or young generation is the next generation of nation that will soon be built nation building. Parents must pay attention to the quality of children's education. Mother is the first teacher for a child and also the greatest motivator for child development. Therefore, the mother is expected to encourage the success of children's education. A housewife who is an unemployed mother has greater time and opportunity to make it happen. It takes capital to do that. Individual characteristics of the intellectual capital of the housewife who is the greatest driver for the success of children's education. And this encouragement will increase as it happens by the increase in social capital owned by housewives. This study will accommodate the intellectual capital owned by housewives to the success of children's education with social capital as a moderate variable. Statistical test tool used is linear regression. The subject is the people of Central Semarang. Samples were taken by random sampling. The data used are primary data collected by questionnaire. The result of Social Capital has an effect on the success of children's education and intellectual capital expressed as excluded variableÂ Keywords: Success of Children's Education, Intellectual Capital housewife, Social Capital